Differential expression of PTEN and PDCD4 tumor suppressors in melanoma and microRNA-21-positive melanoma cells and squamous carcinoma cells - Kao-Hui Liu; Woan-Ruoh Lee; Ya-Ju Hsieh; Chia-Lun Chou; Ming-Chung Jiang; Shing-Chuan Shen (Dermatologica Sinica, 2019)
Background:In vitro cell experiments show that microRNA-21 downregulates the PTEN and PDCD4 tumor suppressor and promote melanoma cell proliferation and invasion. We examined microRNA-21, PTEN, and PDCD4 expressions in various melanoma cells as well as in melanoma specimens to define the actual expression profile of these tumor regulators. Materials and Methods: The microRNA-21, PTEN, and PDCD4 expressions in human keratinocytes and melanoma cells were analyzed by reverse-transcription polymerase chain reaction (RT-PCR) and real-time RT-PCR and immunoblotting. PTEN and PDCD4 expressions in melanoma patients were analyzed by immunohistochemistry. Results: RT-PCR and quantitative real-time PCR assays showed that A375 melanoma cells, squamous cell carcinoma (SCC-25), and SCC-4 skin squamous carcinoma cells expressed a higher level of microRNA-21 than HaCaT human keratinocytes. This inconsistent staining pattern of PTEN and PDCD4 in a melanoma tumor mass is not understandable, because the expression level of microRNA-21 in melanoma specimens are different. The expression of PDCD4 was not inversely correlated with the levels of microRNA-21 in these cells. In addition, we also found that only A2058 cells expressed low PTEN level and that A375, SCC-25, and SCC-4 cells expressed high PTEN levels. Furthermore, expression of PDCD4 was higher in the highly malignant B16F10 mouse melanoma cells than in B16 F0 cells; by contrast, both B16F0 and B16F10 cells expressed PTEN at high levels. Conclusion: Although PDCD4 and PTEN are targets of microRNA-21-dependent inhibition, PTEN and PDCD4 expressions are regulated in a more complex manner in skin cancer; not all microRNA-21-positive skin cancers certainly lose their normal PTEN and PDCD4 tumor suppressor functions.